Menumbuhkan dan Mengembangkan Kepedulian Warga Terhadap Kebersihan Lingkungan Melalui Penghijauan Di Desa Tanjung Putus, Langkat, Sumatera Utara - Mardiati, Mardiati; Saputri, Lilis; Sitepu, Dewi Rulia Br; Susilawati, Enny; Ayumi, Nadia; Ningsih, Yulia; Dewi Siregar, Zulfy Aswita (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
Greening is one of the important activities that must be carried out in dealing with the environmental crisis. Tanjung Breaks Village is one of the villages that is quite active in supporting the greening program. Reforestation activities are carried out to increase public awareness and concern for the cleanliness and beauty of the people in Tanjung Breaks Village. The method used in this activity is socialization regarding the importance of cleanliness and the beauty of the surrounding environment and inviting the community to participate in Gotong Royong and the greening that we are carrying out. In this activity, it is hoped that later the community will become more concerned about the cleanliness and beauty of the environment.